Plasma and urine levels of calcium, phosphorus and magnesium in growing cats - González, Félix Dias; Duarte, Felipe; Brum, Alexandre de; Capp, Cássia; La Rosa, Verônica; Weissheimer, Cristiano; Pigatto, João Antônio; Lacerda, Luciana (Acta Scientiae Veterinariae, 2018)
Feline lower urinary tract disease affects 1% worldwide population of cats. This disease may be predisposed by uroliths formation. Incidence of urolithiasis is related to feeding, mainly to macromineral composition. Balance of calcium, phosphorus and magnesium, and urinary pH are the main factors related to urolithiasis. The present work aims to study the metabolism of those minerals in growing cats, evaluating their plasma and urinary levels. There were used 10 cats of both sexes, 3 month-old, feeding a commercial ration until 1 year-old. Every 30 days, there were collected samples of blood and urine, to determine mineral concentrations and pH and creatinine levels of urine. At same intervals, there were determined the mineral content of the ration. Weekly feed consumption and body weight were registered. Mean levels of calcium, phosphorus and magnesium in plasma were, respectively, 8.77 ± 1.9mg/dL, 7.55 ± 1.8mg/dL and 2.66 ± 0.67mg/dL. Variation along the year is showed. Less variation was that of calcium, followed by magnesium and higher variation was that of phosphorus. Mean values of the minerals in urine, in relation to creatinine, were 1.29 ± 1.0 x10 -2 for Ca, 1.46 ± 1.1 for P and 7.87 ± 7.7 x10-2 for Mg. Ca/P relation in the feed was 2.87 ± 1.2, considered high. Mg content in feed was higher than nutritional requirements. Mean value of urinary pH was 6.25 ± 0.54, considered adequate to prevent urolithiasis by struvite but not to prevent crystal formation of calcium oxalate.